Variability of arterial pressure in acute stroke - a modern approach to the problem - Moskovko, Sergiy; Smotrytska Tеtiana (ScienceRise: Medical Science, 2017)
The question of prospects of using the data of variability of arterial pressure as a base of predictor of development, course and consequences of brain stroke is considered on the base of studied literature. Methods of research: E-data base Medline and PubMed was used for thorough searching for literature on studied questions. Results. The results of scientific literature analysis testify to the connection between variability of arterial pressure and hypertrophy of left ventricle, endothelial dysfunction, development of new cases of auricles fibrillation. According to AP day monitoring, the direct positive connection between the mass index of myocardium of left ventricle and SAP and DAP variability was found. It is indicated, that SAP variability in childhood is a predicator of arterial hypertension development in adulthood. It is shown, that VAP growth can be a predicator of both first and secondary stroke. There are also the data about independent prognostic value of 24-hour variability of arterial pressure as to cardio-vascular events. The duration of study of 24-hour variability of arterial pressure and the number of publications on this question is underlined and insufficiency of information about long-term variability of arterial pressure is noted. It is accented, that in modern assessment of clinical importance of different parameters of arterial pressure variability the change of priority from 2-hour to long-term monitoring of arterial pressure “from visit to visit” is observed. The urgent need in elaboration of accessible methods of assessment of long-term variability of arterial pressure (VAP) that would supply the doctors-practicians with additional information as to the stroke risk and possible consequences is felt. Conclusions. Long-term variability of arterial pressure can be considered as a predictor of stroke development and as independent factor of influence on consequences of undergone brain stroke. It is shown, that the problem of arterial pressure variability is polyhedral and needs further deep study